Pengaruh Kompetensi,Akuntabilitas, Penerapan Kode Etik, dan Gaya Kepemimpinan terhadap Kualitas Audit di Kap di Medan - Namira Ulfrida Rahmi; Tio Hadi; Susilawati Susilawati; Widia Widia; Adam Fredy (Politeknik Ganesha Medan, 2021)
Various cases that occurred in KAP are evidence of problems in the KAP environment that affect the quality of auditors in conducting audits. In conducting audits, independent auditors are required to observe professional principles, including professional responsibility, public interest, integrity, objectivity, competence, and professional prudence. However, various cases that arise within the Public Accounting Firm are one of the reasons for the reduced public trust in Public Accounting Firm services, one of which occurred in the case of violations committed by Hasnil M Yasin & Partners where the director of this Public Accounting Firm committed income tax evasion. in Langkat Regency under the demands of the Public Prosecutor Service along with the Langkat regional secretary Surya Djahisa. Hasnil is suspected of committing a criminal act of corruption that resulted in a loss of state funds of 1 billion rupiahs, therefore the researchers conducted tests in assessing competence, accountability, the application of the Code of Ethics and Leadership Styles that affect the quality of audits at KAP Medan city. The population and samples were taken with the saturation technique. The data analysis model uses structural models, measurement models, path diagram designs, conversion of path diagrams into a system of equations, estimates, the goodness of fit, and others to get the desired results with the help of the WrapPls program. The results showed that the competence, accountability, and code of ethics of Medan public accountants did not affect audit quality. Leadership style has an effect on audit quality at KAP Medan City.